Correlation Near Point of Convergence and Amplitude Accommodation with School Myopia Progression at Near Activity in Badung Regency - Wijayati, Made Paramita; Triningrat, Anak Agung Mas Putrawati; Pemayun, Cok Dewiyani; Handayani, Ariesanti Tri; Suryathi, Ni Made Ari; Surasmiati, Ni Made Ayu (Open Access Macedonian Journal of Medical Sciences, 2022)
School myopia is a term that is used for the development of myopia at school age. The Child Heart and Health Study in England (CHASE) 2010, the prevalence of myopia in Southeast 25,2% at school age. The risk factor for school myopia more complex and one of the environmental factors were near activity. Accommodation, convergence, and miotic pupil are third signs when we look closely. Convergence and accommodation were measured with Near Point of Convergence (NPC) and Amplitude Accommodation (AA). This research aims to know the correlation between NPC and AA with school myopia progression. Research location at Sibang Gede 1st elementary school, Kuta 1st elementary school, Jimbaran 4th elementary school, and Kerobokan Kelod 2nd elementary school. The sample was obtained by Convenience sampling, Stratified Sampling, and Consecutive sampling techniques. Data were analyzed and searching for correlation Near Point of Convergence (NPC), Amplitude Accommodation (AA), and myopia progression was done by bivariate and multivariate analysis with age, gender, and myopic parent. This Research has 125 sample who mostly female 56 %, age at 7 yo 24.8%, median near activity 78 Dh/ week, myopic parent 27.2%. Correlation NPC showed inversely to progression of myopia (NPC Break r = -0.332, p<0.001; NPC Recovery r = -0.335, p<0.001). Correlation AA and progression of myopia showed positive correlation (AA Binocular r = 0.287, p=0.001; AA RE r = 0.226, p=0.017; AA LE r = 0.261, p=0.07). Age has correlation with progression of myopia with (p<0.05). There is a correlation between NPC and AA with school myopia progression at near activity in Badung Regency. Smaller NPC was correlated with progression of myopia and higher AA was correlated with progression of myopia although age was correlated with myopia progression.